1993
DOI: 10.1016/0378-1097(93)90055-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a novel nitrate reductase in the dissimilatory iron-reducing bacterium Geobacter metallireducens

Abstract: Nitrate induced the expression of a membrane-bound nitrate reductase in the strict anaerobe Geobacter metallireducens.A fraction from a DEAE cellulose column which showed nitrate reduetase activity contained polypeptides of M r 18, 36 and 43 K and three c type cytochromes (M r 28, 46 and 68 K). Western and Southern blot analysis revealed no homology between the nitrate reductase from G. metallireducens and the nitrate reductases from respiratory (Escherichia coli) and denitrifying bacteria (Pseudomonas stutzer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…The methyl viologen spectrophotometric assay of Blumle and Zumft (1991) as modified by Naik et al 1993 was used to test for reductase activity. A reaction mixture containing 2.2 ml bicarbonate buffer (10 mM, pH 7.2), 80 µl methyl viologen (1 mg/ml), and 100 µl of the terminal electron acceptor (from stock solutions prepared as described below) was sparged for 5 min with oxygen-free dinitrogen in a Thunberg cuvette.…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…The methyl viologen spectrophotometric assay of Blumle and Zumft (1991) as modified by Naik et al 1993 was used to test for reductase activity. A reaction mixture containing 2.2 ml bicarbonate buffer (10 mM, pH 7.2), 80 µl methyl viologen (1 mg/ml), and 100 µl of the terminal electron acceptor (from stock solutions prepared as described below) was sparged for 5 min with oxygen-free dinitrogen in a Thunberg cuvette.…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…Initial biochemical investigations have found that nitrate reductase activity is limited to cells grown on nitrate. This activity is membraneassociated and not solubilized by Triton X 100 or heat, and four c-type cytochromes are overexpressed (Naik et al 1993). Southern blot analysis using narG from E. coli as a probe, and Western blot analyses with antibodies to the holoenzyme from Pseudomonas stutzeri have not revealed a similar type of nitrate reductase in G. metallireducens (Naik et al 1993).…”
Section: Introductionmentioning
confidence: 95%
“…This activity is membraneassociated and not solubilized by Triton X 100 or heat, and four c-type cytochromes are overexpressed (Naik et al 1993). Southern blot analysis using narG from E. coli as a probe, and Western blot analyses with antibodies to the holoenzyme from Pseudomonas stutzeri have not revealed a similar type of nitrate reductase in G. metallireducens (Naik et al 1993). In addition, cytochrome b has not been detected spectrophotometrically in whole cells, cytoplasmic fractions, membrane fractions, or in preparations of partially purified enzyme (Naik et al 1993).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The presence of c-type cytochrome(s) was shown by spectral analysis of whole-cell suspensions and membrane fractions of G. metallireducens and G. sulfurreducens (Lovley et al, 1993 ;Naik et al, 1993 ;Caccavo et al, 1994 ;Seeliger et al, 1998). In contrast, cells of P. propionicus lack c-type cytochromes (Schink, 1984).…”
mentioning
confidence: 99%